Interpretation of vector analysis nomograms for nutrient diagnosis of forest tree species - López-López, Miguel Ángel; Alvarado-López, Jorge (Instituto de Ecología, A.C., 2016)
The interpretation of the nomograms from the vector analysis technique for nutrient status diagnosis of preformed growth forest tree species frequently is a difficult task that may lead in some cases to vague or even unsatisfactory conclusions. The present document contains a guide to help nutrient diagnosticians to interpret such nomograms. As compared with the existing tabular models for nomogram interpretation, this guide includes a higher amount of possible vectors, it provides a wider spectrum of interpretation possibilities for each of the vectors, and discriminates the interpretation of the nomograms according to the level of manipulation of the nutrient being analyzed. Furthermore, if it applies, the status of the nutrient before and after the application of treatments is defined.